Transcriptional activity of the giant barrel sponge, Xestospongia muta Holobiont: molecular evidence for metabolic interchange - Fiore, Cara L.; Labrie, Micheline; Jarett, Jessica K.; Lesser, Michael P. (Frontiers in Microbiology, 2015)
Compared to our understanding of the taxonomic composition of the symbiotic microbes in marine sponges, the functional diversity of these symbionts is largely unknown. Furthermore, the application of genomic, transcriptomic, and proteomic techniques to functional questions on sponge host-symbiont interactions is in its infancy. In this study, we generated a transcriptome for the host and a metatranscriptome of its microbial symbionts for the giant barrel sponge, Xestospongia muta, from the Caribbean. In combination with a gene-specific approach, our goals were to 1) characterize genetic evidence for nitrogen cycling in X. muta, an important limiting nutrient on coral reefs 2) identify which prokaryotic symbiont lineages are metabolically active and, 3) characterize the metabolic potential of the prokaryotic community. Xestospongia muta expresses genes from multiple nitrogen transformation pathways that when combined with the abundance of this sponge, and previous data on dissolved inorganic nitrogen fluxes, shows that this sponge is an important contributor to nitrogen cycling on coral reefs. Additionally, we observed significant differences in gene expression of the archaeal amoA gene, which is involved in ammonia oxidation, between coral reef locations consistent with differences in the fluxes of dissolved inorganic nitrogen previously reported. In regards to symbiont metabolic potential, the genes in the biosynthetic pathways of several amino acids were present in the prokaryotic metatranscriptome dataset but in the host-derived transcripts only the catabolic reactions for these amino acids were present. A similar pattern was observed for the B vitamins (riboflavin, biotin, thiamin, cobalamin). These results expand our understanding of biogeochemical cycling in sponges, and the metabolic interchange highlighted here advances the field of symbiont physiology by elucidating specific metabolic pathways where there is high potential for host-prokaryote interactions.